2022
DOI: 10.1002/qre.3099
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate cumulative sum control chart for compositional data with known and estimated process parameters

Abstract: This article uses the classic multivariate cumulative sum (MCUSUM$\mathrm{MCUSUM}$) chart scheme proposed by Crossier (1988) to present a new modified MCUSUM$\mathrm{MCUSUM}$ chart for compositional data (CoDa$\mathrm{CoDa}$). For this purpose, the data are first transformed using isometric log‐ratio (ilr$\operatorname{ilr}$) coordinates representation to eliminate the constant sum constraint of CoDa$\mathrm{CoDa}$. The MCUSUM$\mathrm{MCUSUM}$‐CoDa$\mathrm{CoDa}$ control chart has been defined along with the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Based on APY, the most recent topic from the cluster is "compositional data", with an APY score of 2019.6. Hu et al [60] and Williams et al [47] feature as the top-cited articles on measurement error and process quality in our list, cited 49 and 230 times, respectively, while Imran et al [61] (2022) article is the most recent on compositional data.…”
Section: Cluster 7: Measurement Error and Process Qualitymentioning
confidence: 95%
“…Based on APY, the most recent topic from the cluster is "compositional data", with an APY score of 2019.6. Hu et al [60] and Williams et al [47] feature as the top-cited articles on measurement error and process quality in our list, cited 49 and 230 times, respectively, while Imran et al [61] (2022) article is the most recent on compositional data.…”
Section: Cluster 7: Measurement Error and Process Qualitymentioning
confidence: 95%
“…To assess the MCUSUM-CoDa CC's run-length efficiency, the authors implement a Markov chain approximation suggested by Crosier [42]. The Markov Chain model needed to measure the MCUSUM-CoDa chart's ARL is given in [43].…”
Section: Multivariate Cusum CC For Compositional Datamentioning
confidence: 99%
“…The multivariate exponentially weighted moving average (MEWMA) CoDa CC has been studied by Tran et al, 23 , while Zaidi et al 24 evaluated the impact of ME on the MEWMA CCs for CoDa. The estimation of the parameters for the multivariate cumulative sum (MCUSUM) CC for CoDa has been studied 25 and also the effects of ME on the MCUSUM CoDa CC has been evaluated. 26 The MEWMA CC for CoDa has been studied using VSS.…”
Section: Introductionmentioning
confidence: 99%
“….00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 0 25. 202.04 369.15 369.15 357.35 357.35 228.90 228.90 199.29 368.45 368.45 356.65 356.65 228.20 228.20 196.97 363.15 363.26 350.87 350.94 223.03 223.13 0.50 129.68 368.30 368.30 345.40 345.40 157.97 157.97 122.53 367.52 367.52 344.62 344.62 157.19 157.19 118.93 362.72 362.82 339.39 339.44 152.51 152.59 0.75 90.82 367.46 367.46 334.10 334.10 116.30 116.30 84.55 .00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 370.00 0.25 221.24 361.35 365.56 357.35 357.35 328.68 346.46 199.29 360.65 364.86 356.65 356.65 327.98 345.76 196.97 355.35 359.67 350.87 350.94 322.81 340.69 0.50 146.48 353.03 361.21 345.40 345.40 294.46 325.30 122.53 352.25 360.43 344.62 344.62 293.68 324.52 118.93 347.45 355.72 339.39 339.44 289.00 319.93 0.75 105.22 345.03 356.95 334.10 334.10 265.73 306.20 84.55 .66 313.25 313.25 220.27 273.10 47.50 328.90 347.67 312.26 312.26 219.27 272.10 46.40 326.00 344.83 309.10 309.13 216.44 269.32 1.50 48.35 322.73 344.64 303.62 303.62 202.04 258.67 38.01 321.67 343.58 302.56 302.56 200.98 257.61 37.12 319.27 341.23 299.94 299.97 198.64 255.31 1.75 38.24 315.82 340.69 294.46 294.46 186.11 245.45 31.04 314.69 339.56 293.33 293.33 184.97 244.31 30.93 313.09 337.99 291.58 291.60 183.41 242.78 2.00 30.11 309.15 336.82 285.76 285.76 172.07 233.28 26.59 307.88 335.55 284.48 284.48 170.80 232.01 26.46 306.85 334.54 283.36 283.37 169.79 231.02 ARL and ATS curves corresponding to the without measurement error scenario.…”
mentioning
confidence: 99%